Comorbidity between depression and inflammatory bowel disease explained by immune-inflammatory, oxidative, and nitrosative stress; tryptophan catabolite; and gut–brain pathways. (26th August 2015) - Martin-Subero, Marta; Anderson, George; Kanchanatawan, Buranee; Berk, Michael; Maes, Michael
Abstract : The nature of depression has recently been reconceptualized, being conceived as the clinical expression of activated immune-inflammatory, oxidative, and nitrosative stress (IO&NS) pathways, including tryptophan catabolite (TRYCAT), autoimmune, and gut–brain pathways. IO&NS pathways are similarly integral to the pathogenesis of inflammatory bowel disease (IBD). The increased depression prevalence in IBD associates with a lower quality of life and increased morbidity in IBD, highlighting the role of depression in modulating the pathophysiology of IBD.This review covers data within such a wider conceptualization that better explains the heightened co-occurrence of IBD and depression. Common IO&NS underpinning between both disorders is evidenced by increased pro-inflammatory cytokine levels, eg, interleukin-1 (IL-1) and tumor necrosis factor-α, IL-6 trans-signalling; Th-1- and Th-17-like responses; neopterin and soluble IL-2 receptor levels; positive acute phase reactants (haptoglobin and C-reactive protein); lowered levels of negative acute phase reactants (albumin, transferrin, zinc) and anti-inflammatory cytokines (IL-10 and transforming growth factor-β); increased O&NS with damage to lipids, proteinsm and DNA; increased production of nitric oxide (NO) and inducible NO synthase; lowered plasma tryptophan but increased TRYCAT levels; autoimmune responses; and increased bacterial translocation. As such, heightened IO&NS processes in depression overlap with the biological underpinnings of IBD, potentially explaining their increased co-occurrence. This supports the perspective that there is a spectrum of IO&NS disorders that includes depression, both as an emergent comorbidity and as a contributor to IO&NS processes. Such a frame of reference has treatment implications for IBD when "comorbid" with depression.